2011
DOI: 10.1111/j.1365-2109.2011.02938.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of temperature, salinity and density on the growth and feed utilization of Nile tilapia juveniles (Oreochromis niloticus)

Abstract: Based on Box-Behnken experimental design and response surface method, the joint effect of temperature (16-36°C), salinity (0-22 ppt) and rearing density (200-1000 fish.m À3 ) on the specific growth rate (SGR) and feed conversion rate (FCR) of Nile tilapia juveniles were studied under laboratory conditions. The entire experiment lasted for 1 month (30 days). Results showed that the linear and quadratic effects of temperature, salinity on both growth and feed utilization were highly statistically significant (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Euryhaline fish are very tolerant to water salinity, both during the embryonic development and larval growth (Alderdice ). An excellent example of such a fish is the Nile tilapia Oreochromis niloticus , which – despite being a freshwater fish – tolerates water salinity up to 20 ppt (Watanabe & Kuo ; Watanabe, Kuo & Huang ; Suresh & Lin ; El‐Sayed ; Jun, Pao, Haizhen, Ruiwei & Hui ). Likewise, early developmental stages of such fish as Eurasian perch Perca fluviatilis , burbot Lota lota , salmonid fish ( Salmonidae ) (Morgan & Iwama ), whitefish Coregonus lavaretus , stickleback (Klinkhardt & Winkler ; Jobling ) are much more tolerant to water salinity than cyprinid fish.…”
Section: Discussionmentioning
confidence: 99%
“…Euryhaline fish are very tolerant to water salinity, both during the embryonic development and larval growth (Alderdice ). An excellent example of such a fish is the Nile tilapia Oreochromis niloticus , which – despite being a freshwater fish – tolerates water salinity up to 20 ppt (Watanabe & Kuo ; Watanabe, Kuo & Huang ; Suresh & Lin ; El‐Sayed ; Jun, Pao, Haizhen, Ruiwei & Hui ). Likewise, early developmental stages of such fish as Eurasian perch Perca fluviatilis , burbot Lota lota , salmonid fish ( Salmonidae ) (Morgan & Iwama ), whitefish Coregonus lavaretus , stickleback (Klinkhardt & Winkler ; Jobling ) are much more tolerant to water salinity than cyprinid fish.…”
Section: Discussionmentioning
confidence: 99%
“…Among abiotic factors, any change in ambient water temperature has the greatest effect on the physiological properties of fish (Johnston, 2006;Arnason et al, 2009;Jun et al, 2012;da Costa et al, 2016;Mazumder et al, 2015b;Zhang et al, 2015). Quite apart from temperature, the quality of food is thought to be another important determinant of fish physiology and ultimately their growth (Kooijman, 2000;Byström et al, 2006;Englund et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…() found that the interactive effects of temperature and salinity were significant on the hatching of the fertilized eggs of Sepia pharaonis . Interaction can significantly change the growth and feed utilization of tilapia juveniles (Jun et al., ; Likongwe et al., ). Effects of interaction were significant during the early development of Pinctada martensii (Wang et al., ), Argopecten irradia (Tettelbach & Rhodes, ) and Ruditapes philippinarum (Sang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the interaction of different environmental factors causes synergetic effects on aquatic animals (Fiess et al, 2007;Jun et al, 2012). Full factorial designs are often used to study the interaction between temperature and salinity (Likongwe et al, 1996;Watanabe et al, 1993), showing the quadratic effects of factors or a combination of optimal factor levels (Jun et al, 2012).…”
Section: ) and Thus Become The New Species In Grouper Aquaculturmentioning
confidence: 99%
See 1 more Smart Citation